The Play of the self - Bogue, Ronald, 1948-; Spariosu, Mihai (SUNY series, the margins of literature., 1994)
"The book covers extraordinary ground in literature, the arts, philosophy, and even the social sciences. The concern about the issue of self and the representations of self brings far-reaching ideas together in the most surprising and mutually illuminating ways. Poststructuralist and postmodernist critiques of self-identity have made the topic controversial and broadly relevant to all the fields represented. Extreme statements abound on both sides of the argument, and this book succeeds in marshaling subtle and nuanced thought on the topic. Each essay is neatly self-contained, remarkably relevant to other essays in the collection, and a model of illuminating argument, careful scholarship, and attractive writing."--Book cover